Implementation of a Trauma Quality Improvement Program Communications Package Decreases Time-to-Operation for Facial Trauma. (June 2019) - Keller, Patrick R.; Schneeberger, Steven; Drolet, Brian C.; Al Kassis, Salam; Bennett Pearce, F.; Perdikis, Galen
Abstract : Introduction: Facial trauma is common and carries significant morbidity and cost. Suboptimal interdisciplinary communication is associated with negative health outcomes. This study evaluates the clinical impact of implementation of American College of Surgeons Trauma Quality Improvement Program (TQIP) interdisciplinary communication guidelines between facial surgery and trauma teams. Methods: Patients with facial trauma presenting to our level 1 trauma center between May and December 2017 were included (N = 812) and split into 3 groups, each anonymously representing a service that treats facial trauma. Services 1 and 2 were controls, and service 3 adopted TQIP communication guidelines. Mean and slope of time-to-operation (TTO) and mean length of stay were assessed 106 days before (n = 95) and 107 days after (n = 77) implementation. Results: For service 3, mean TTO decreased significantly from 6.2 to 2.9 days ( P = 0.005) after implementation of the communication intervention. There was no significant difference in mean TTO preimplementation versus postimplementation in either control cohort, including service 1 (4.6 vs 4.9 days; P = 0.59) and service 2 (4.2 vs 4.5 days; P = 0.62). Average length of stay did not differ significantly between the preintervention versus postintervention in any service (service 1: 9.0 vs 8.3 days, P = 0.43; service 2: 4.6 vs 6.6 days, P = 0.85; service 3: 6.7 vs 6.4 days, P = 0.45). Conclusion: Our study demonstrates that cost-free TQIP-guided improvement in interdisciplinary communication between the trauma service and a consulting surgical specialist decreases TTO for patients with operative facial trauma. Health care providers should develop strong well-defined communication channels between collaborating teams involved in patient care to optimize patient clinical outcomes.